LANGUAGE AS SEMANTIC GOVERNANCE: FROM PAVLOV’S SECOND SIGNALING SYSTEM TO AN ODAM TILI THEORY OF SOCIAL CONTROL - Mahmudjon Kuchkarov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines language not merely as a medium of communication but as a mechanism of cognitive mediation and social regulation. Starting from Ivan Pavlov’s concept of the second signaling system, the paper argues that verbal signs function as specifically human signals that reorganize perception, abstraction, and response. Contemporary research in language and cognition, discourse studies, and behavioral framing supports the broader claim that linguistic form influences how humans categorize reality, allocate attention, infer norms, and act within institutional environments. Building on this literature, the paper introduces the Odam Tili perspective associated with Dr. Mahmudjon Kuchkarov, according to which language should not be reduced to an arbitrary symbolic code but understood as emerging from a deeper relation among embodied action, sound, and meaning. From this standpoint, language becomes not only a representational tool but a governing infrastructure: it can align perception with lived experience, or detach thought from it. The article proposes the concept of semantic governance to describe the regulation of individuals and societies through naming, framing, and discourse control. It concludes that any serious theory of power, cognition, or human freedom must treat language as a central site of social struggle rather than a secondary cultural ornament.